2012
DOI: 10.1111/j.1365-3156.2012.03016.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax Duffy binding protein: baseline antibody responses and parasite polymorphisms in a well‐consolidated settlement of the Amazon Region

Abstract: Abstractobjective To investigate risk factors associated with the acquisition of antibodies against Plasmodium vivax Duffy binding protein (PvDBP) -a leading malaria vaccine candidate -in a well-consolidated agricultural settlement of the Brazilian Amazon Region and to determine the sequence diversity of the PvDBP ligand domain (DBP II ) within the local malaria parasite population.methods Demographic, epidemiological and clinical data were collected from 541 volunteers using a structured questionnaire. Malari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(77 citation statements)
references
References 42 publications
5
69
0
3
Order By: Relevance
“…In a cross-sectional study, Kano et al [23] found no evidence for any association between IgG responses to PvDBPII-IV Sal 1 and P. vivax infection. One study by Souza-Silva et al provided data from two cross-sectional surveys conducted in the same study site in Brazil [29].…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In a cross-sectional study, Kano et al [23] found no evidence for any association between IgG responses to PvDBPII-IV Sal 1 and P. vivax infection. One study by Souza-Silva et al provided data from two cross-sectional surveys conducted in the same study site in Brazil [29].…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
“…The association of antibodies to PvDBP region II-IV (PvDBPII-IV) and P. vivax infection was examined in one cross-sectional study [23] and one cohort study that also provided two sets of cross-sectional data [29]. In a cross-sectional study, Kano et al [23] found no evidence for any association between IgG responses to PvDBPII-IV Sal 1 and P. vivax infection.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
See 3 more Smart Citations